Thinking complex interconnections: Transition, nexus and geography - Schwanen, T (Wiley, 2017)
More than ever is Geography surrounded by interdisciplinary movements claiming expertise with regard to the interconnections among nature, society and technology. These movements ask questions from Geography and geographers about if and how they can contribute to those movements and what form collaboration might take. This paper analyses Human Geography's interactions with research on sustainability transitions since the early 2000s to think through future interactions between Geography and research on the water–energy–food nexus. It shows that concepts, ideas, logics and methods have travelled from Human Geography into Transition Studies but that exchange between them has so far been partial and asymmetrical. Arguing that common ideas about how interdisciplinarity can be encouraged might be insufficient to change this situation, the paper develops ideas from Stengers, Whitehead, Foucault and others to explain the relations between Human Geography and Transition Studies in terms of modes of abstraction in an evolving ecology of power relations. It makes a case for slowing down modes of abstraction and proposes some ideas for slow collaborative research on sustainability transitions in contact zones. Implications for how Geography and geographers might engage with interdisciplinary nexus research are outlined.